2016
DOI: 10.3389/fpsyg.2016.01412
|View full text |Cite
|
Sign up to set email alerts
|

Gender Effects in Young Road Users on Road Safety Attitudes, Behaviors and Risk Perception

Abstract: In the present study, we investigated gender-related effects on road safety attitudes in 2681 young drivers (1458 males, 54.4%; aged 18–22) who filled out several scales assessing attitudes toward road safety issues, driving behavior in specific hypothetical situations, accident risk perception, and concerns about such a risk. We focused only on young drivers to better understand the role of gender in road safety attitudes in a period of life in which risky behaviors are widespread for males and females. Indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 51 publications
(56 reference statements)
9
111
1
6
Order By: Relevance
“…We add that in all ANOVA comparisons on road users, we wanted to evaluate the potential gender effects. Numerous studies showed the gender-related effects on road safety attitudes (Classen, Wang, Crizzle, Winter, & Lanford, 2012), in particular in young drivers (Cordellieri et al, 2016). Although our results confirm that male young drivers are more prone to accept speeding, traffic violations and drugs and alcohol use by the driver, these effects do not significantly affect the differences among road users.…”
Section: Discussioncontrasting
confidence: 75%
“…We add that in all ANOVA comparisons on road users, we wanted to evaluate the potential gender effects. Numerous studies showed the gender-related effects on road safety attitudes (Classen, Wang, Crizzle, Winter, & Lanford, 2012), in particular in young drivers (Cordellieri et al, 2016). Although our results confirm that male young drivers are more prone to accept speeding, traffic violations and drugs and alcohol use by the driver, these effects do not significantly affect the differences among road users.…”
Section: Discussioncontrasting
confidence: 75%
“…Studies also documented clear variations in the accident involvement and risky driving behaviors between the two genders in favor of females [25,[29][30][31]. Though males are frequently considered as skilled drivers, they often engage in risky behaviors including trespassing speed limits, reckless overtaking, non-use of seatbelts and driving under the influence of alcohol [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…Though males are frequently considered as skilled drivers, they often engage in risky behaviors including trespassing speed limits, reckless overtaking, non-use of seatbelts and driving under the influence of alcohol [25,29]. Male drivers also tend to have lower attention, impatience and risk perception than females [25,30].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, actualmente no se conoce bien los motivos de esta asociación, se han planteado diversas hipótesis en comparación con las mujeres, los peatones masculinos están involucrados en colisiones de mayor severidad intrínseca. Por ejemplo, se ha informado de colisiones nocturnas en las que los hombres pueden verse involucrados con mayor frecuencia, porque las mujeres tienden a caminar o transitar menos en horas nocturnas y en muchas ocasiones estas colisiones son más severas que las que ocurren durante el día (15,16) .…”
Section: Discussionunclassified